2022
DOI: 10.1007/s12649-022-01721-0
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Look at Bioproducts Co-cultured Under Solid State Fermentation and Their Challenges and Industrial Applications

Abstract: The production of bioproducts from microorganisms is a common practice in many industries for a long time now. In recent years, studies have proved that co-culturing microorganisms increase the yield of products by synergistically degrading the solid substrate in comparison with individual cultures. The review highlights the benefits of co-culturing microorganisms using solid state fermentation (SSF) to achieve higher productivity. Filamentous fungi of genus Trichoderma, Penicillium, and Aspergillus are extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 107 publications
0
10
0
1
Order By: Relevance
“…LYM-1 to its monomer N -acetylglucosamine as the main carbon source instead of Glc. However, Rib was not detected in AP-WSPs, and the proportion of Rib in PsL/AP-WSPs was higher, owing to the benefit of co-culture fermentation ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…LYM-1 to its monomer N -acetylglucosamine as the main carbon source instead of Glc. However, Rib was not detected in AP-WSPs, and the proportion of Rib in PsL/AP-WSPs was higher, owing to the benefit of co-culture fermentation ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…From these results, further approaches including transcriptomic analysis of pigment biosynthesis and genomics-driven optimization processes should be considered, so that productivity parameters can be also validated on natural substrates. Additionally, co-cultures under SSF could be considered a promising strategy by which to increase pigment production yields [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may generate much interest in fermenting plant protein sources for making inexpensive commercial formulations. However, contamination is quite a challenge during the co‐culturing process, hence; the synergism of each species needs to be studied prior to culture to reduce the antagonism effects that affect the quality of products 167 . It is also suggested for manipulation of microbial strains to have higher synergy with each other.…”
Section: Opportunities For a Nigermentioning
confidence: 99%
“…Improving the fungal strain and/or re-designing its metabolic process helps to increase its utilization in biotechnological aspects that can be achieved using modern genetic engineering technology. Prabhu et al 167 reported that the recombinant or mutated strains had a higher tolerance to environmental variations and the ability in improving product quality. Richter et al 168 reported that the timing of secondary metabolite formation by A. niger was controlled effectively by an engineering tool called the Tet-on system, which not only increases the purity of products but also the yield.…”
Section: Genetic Engineeringmentioning
confidence: 99%